On Defectors and Melancholic Migrants: Life and (Post)Memory Writing in "Árbol de familia" by María Rosa Lojo - Moszczyńska-Dürst, Katarzyna (Madrygal. Revista de Estudios Gallegos, 2026)
Árbol de familia, by the Galician-Argentine author María Rosa Lojo, is a meditation on the persistence of memory and the impact of migratory narratives on the life and identity of various generations, as well as a tribute to her relatives, who had to adopt strategies as outcasts, defectors, rebels, and melancholic migrants (Ahmed). This community, which has not fully undergone the mourning process, is characterised by a resistance to acknowledging and processing ungrieved losses from the past. These wounds continue to exert a persistent and silent influence on individual and collective identity. In this sense, melancholia is not an individual emotional condition, but rather a collective phenomenon that transcends generations (Butler, Ahmed, Hirsch). According to Freud, melancholy differs from mourning in that the former involves an inability to detach from the lost object, leading to a prolonged and pathological identification with the loss. In the case of forced migration first, and the republican exile afterwards, which affects the auto(bio)graphical narration of the migrants and their descendants, this melancholia –both individual and collective– manifests as a frozen memory, an incomplete mourning of profound political implications that disturbs collective happiness
Keywords: Auto(bio)graphy; (Post)memory; Defector; Migration; Melancholia